Silver Nanoparticles Mediated through Aqueous Leaf Extract of Ageratina adenophora Inhibit Proliferation and Induce Apoptosis in Human Ovarian Teratocarcinoma Cell Line PA-1 - Latha Maheswari, B.; Mani, N.; Karthika, S.; Kavikala, N. (Asian Journal of Chemistry, 2022)
An enhanced anticancer properties of Ageratina adenophora mediated silver nanoparticles (AgNPs) were evaluated in the present study. The biogenic AgNPs effectively inhibited the viability and proliferation of ovarian teratocarcinoma cells (PA-1) by significantly increasing the initiation of apoptosis. The AgNPs were synthesized with the phytochemicals present in aqueous extract of Ageratina adenophora leaves which performed the dual function of reducing silver ions as well as the capping the nanoparticles. Characterization of nanoparticles with UV-vis spectroscopy revealed surface plasmon resonance peak at 470 nm. Fourier transform infrared spectrum showed the presence of functional groups such as alcohol, aldehyde, alkane, aromatic amines and phenolic compounds. X-Ray diffraction (XRD) analysis revealed the crystalline nature and face centred cubic structure of AgNPs. The size, morphology and distribution of AgNPs were confirmed with scanning electron microscope (SEM). Further, dynamic light scattering (DLS) and zeta potential measurements also confirmed the size and charge of the synthesized nanoparticles. The AgNPs significantly increased the cytotoxicity and inhibited the proliferation of PA-1 cells. Apoptosis of PA-1 cells were increased with treatment of AgNPs. The increased cytotoxicity of PA-1 cells was due to the synergistic activity of phytochemicals and AgNPs. Hence, the current research on the silver nanoparticles mediated through A. adenophora leaf extract could be an effective alternative in treatment of ovarian cancer.